2019
DOI: 10.32604/biocell.2019.08407
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 attenuates anxiety-like behavior in long-term ovariectomized rats with unpredictable mild stress

Abstract: The impact of various vitamin D3 (VD3) doses (1.0, 2.5, or 5 mg/kg, s.c.) in mitigating the negative consequences of chronic unpredictable mild stress (CUMS) was investigated. Adult female rats with long-term estrogen deficiency were assessed using the sucrose preference test (SPT), the elevated plus-maze (EPM), the light/dark test (LDT), and the open-field test (OFT) to measure anhedonia-like and anxiety-like behavior. The corticosterone (CS) and adrenocorticotrophic hormone (ACTH) concentrations in blood ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…VD supplementation can improve anxiety symptoms in depressive patients with low VD levels after 6 months of intervention [ 71 ]. Vitamin D 3 (5.0 mg/kg) administration seems to attenuate the anxiety-like profile in long-term ovariectomized adult rats subjected to chronic unpredictable mild stress [ 72 ]. It is suggested that VD could potentially be used as a therapeutic agent to prevent anxiety in postmenopausal women, and the mechanism of action of l -pyroglutamic acid requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…VD supplementation can improve anxiety symptoms in depressive patients with low VD levels after 6 months of intervention [ 71 ]. Vitamin D 3 (5.0 mg/kg) administration seems to attenuate the anxiety-like profile in long-term ovariectomized adult rats subjected to chronic unpredictable mild stress [ 72 ]. It is suggested that VD could potentially be used as a therapeutic agent to prevent anxiety in postmenopausal women, and the mechanism of action of l -pyroglutamic acid requires further exploration.…”
Section: Discussionmentioning
confidence: 99%